Évaluation quantitative et mise au point d'un SIG sur la structuration du paysage bocager de Ras Djebel dans le sahel de Bizerte (Tunisie) - Brahim Jaziri (Physio-Géo)
This contribution of landscape geography in the Ras Djebel sector is based on proven indicators for characterization of the hedgerows, in particular the weighted density index (Dbp) and the connectivity index (I(Co)), which were calculated for mesh sizes of one hectare. The combination of these two indices gives particularly interesting results. The most wooded meshes (tight network of heavily connected hedges) are located in the low coastal plains of the north-central and northeast parts of the study area. In the back, a band of variously wooded meshes forms a transition with the open fields covering the hills located inland (altitude above 150 m). In addition to the definition and cartographic representation of the characteristics of the bocage, the article proposes a methodological reflection on the implementation of the indices and the development of the approaches.